MODEL RESOLUSI KONFLIK KAWASAN REGISTER 45 MESUJI LAMPUNG BERBASIS HUTAN TANAMAN RAKYAT - Komang Jaka Ferdian (Program Magister Ilmu Politik, Universitas Diponegoro, 2017)
Agrarian conflicts in Indonesia, one of which occurred in the region registers 45 Mesuji Lampung. The conflict in the region registers 45 result people are not getting their rights as citizens. The problem area management register 45 that conflict has reached a scale where there is a negative impact on residents who often get unilateral acts of intimidation and arrest of the security forces. The conflict that left would pose a threat to one of the parties, special nature of conflict can be widened up to the global level, there is a violence that resulted from one of the parties. The purpose of this study is to map the conflict in the region registers 45 Mesuji of Lampung and explain the model of conflict resolution in the region register 45 based on Forest Plantation. Conflict in the region register 45 involves PT. Silva Inhutani, Community Register 45, State / Government, Land Speculators, thuggery, Megoupak and Media. Model of conflict resolution that can be done through Forest Plantation. The positive side is going to cause, among others, conflict resolution, improvement in the economic sector, development environments, forming jobs, alleviate poverty and improve food security in Mesuji district. Keywords:Land Conflict; Mapping Conflict; Conflict Resolution; Mediation; Forest Plantation